2010
DOI: 10.1111/j.1445-6664.2010.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential allelopathic effects of Mikania micrantha on the seed germination and seedling growth of Coix lacryma‐jobi

Abstract: The allelopathic potential of Mikania micrantha H.B.K. to affect the seed germination and seedling growth of Coix lacryma-jobi L. was investigated. Water-soluble allelopathic substances were found in the water extracts of M. micrantha.The effect of the water extracts on the seed germination and seedling growth of C. lacryma-jobi was concentration-dependent. The water extracts from the different plant parts (leaf, stem, and root) of M. micrantha differed in their effect on the germination and seedling growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…The allelochemical isolated from Ficus microcarpa inhibits the growth of Chlorella pyrenoidosa and the primary active fraction was identified as 2-propyl phenol [11]. The allelochemical extracts of invasive plants may inhibit the seed germination and seedling growth of acceptor plants and also exert effects on their antioxidant enzyme activities and malondialdehyde (MDA) contents [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The allelochemical isolated from Ficus microcarpa inhibits the growth of Chlorella pyrenoidosa and the primary active fraction was identified as 2-propyl phenol [11]. The allelochemical extracts of invasive plants may inhibit the seed germination and seedling growth of acceptor plants and also exert effects on their antioxidant enzyme activities and malondialdehyde (MDA) contents [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that water extracts of donor plants could inhibit the seed germination and seedling growth of receptor plants through the regulation of anti‐oxidase activity, such as POD and CAT in the cells. The growth inhibition of the receptor plant seedlings is probably related to injury after oxidization of the cell membranes with the increase of MDA content . Huang et al .…”
Section: Resultsmentioning
confidence: 99%
“…Li & Jin (2010) also reported that the stem extracts of Mikania micrantha showed higher inhibitory activity than the leaf extracts. However, the leaves appear to be the most consistent source of chemicals involved in phytotoxicity, producing the greatest inhibitory effects on target species (Souza et al, 2010;Khan et al, 2011).…”
Section: Effect Of Serjania Lethalis Ethanolic Extract On Weed Controlmentioning
confidence: 93%
“…Phytotoxic activity depends on the concentration of the extracts and the plant organ from which they were extracted (Li & Jin, 2010). Different plant tissues, such as leaves, stems and roots, can release different amounts of allelochemicals into the surrounding environment (Souza Filho, 2006).…”
Section: Effect Of Serjania Lethalis Ethanolic Extract On Weed Controlmentioning
confidence: 99%